ANALYSIS OF CONTROL ROD STUCK INITIATING EVENT AT PAKISTAN RESEARCH REACTOR-2 BY USING PSA - Quddus, A.; Ahmed, A.; Raza, S. S.; Waheed, K.; Chaudhary, K. S.; Akram, Z. (The Nucleus, 2020)
Probabilistic Safety Analysis (PSA) is an analytic method used for nuclear reactors safety. Large developments have been made in this field for better understanding about risks of those events about which there is often very little information is known. This analysis is being increasingly used to complement the deterministic approach in nuclear safety. This paper presents the work and results of level-1 PSA performed for Pakistan Research Reactor-2 (PARR-2) located in PINSTECH Complex Nilore, Islamabad, Pakistan. Event tree was drawn to study the response of the system against initiating event while fault tree were used for modeling of failure of the safety of system. Generic and maintenance data of PARR-2 were used to calculate the frequencies of the accident that may cause core damage. Thus the total frequency of core damage for control rod as initiating event was found to be 1.25E-06per reactor year. These results were used to identify the system and components of PARR-2 that are important for the safety the reactor.